Digital transformation strategy making in pre-digital organizations: The case of a financial services provider - Chanias, Simon; Myers, Michael D.; Hess, Thomas (The journal of strategic information systems, 2019)
•Digital strategy making is different from upfront strategic planning.•A digital transformation strategy is continuously in the making.•The crafting of a digital transformation strategy is a highly dynamic process.•We propose a process model for pre-digital organizations in traditional industries. The formulation and implementation of a digital transformation strategy (DTS) has become a key concern for many pre-digital organizations across traditional industries, but how such a strategy can be developed remains an open question. We used interpretive in-depth case study research to study how a European financial services provider has formulated and implemented a DTS. By focusing on the underlying processes and strategizing activities, we show that digital strategy making not only represents a break with the conventions of upfront strategic information systems (IS) planning, but reveals a new extreme of emergent strategy making. Specifically, we conclude that a DTS is continuously in the making, with no foreseeable end. By building on theory from IS strategizing and strategy-as-practice literature, we theorize an integrated process/activity model that characterizes DTS formulation and implementation in pre-digital organizations. Our model shows that the crafting of a DTS is a highly dynamic process involving iterating between learning and doing.